Indigenous and Rural Knowledge in Secondary Science Education: A Review from the Global South - Kumar, Vishal; Choudhary, Sanjiv Kumar (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Science education worldwide is under increasing pressure to respond to the urgent challenges of sustainability, cultural diversity, and knowledge justice. Dominant science curricula, shaped by globalized standards, often exclude the knowledge systems of Indigenous and rural communities, undermining both local relevance and ecological insight. This paper examines how secondary science education research in the Global South engages with Indigenous and rural knowledge systems. Using a structured scoping review approach, eight empirical studies were analyzed through thematic synthesis to identify conceptual trends, pedagogical strategies, and systemic tensions. The review finds a growing effort to reframe science education through culturally rooted pedagogies, integration of traditional ecological knowledge, and curriculum designs that support epistemic plurality. These innovations, however, emerge within constraining conditions: fragmented policy implementation, teacher uncertainty, and structural inequities. The analysis also highlights underexplored regions and unresolved tensions between standardization and local responsiveness. Taken together, the findings reveal both the possibilities and limitations of current reform efforts. This study contributes to global conversations on reimagining science education as a practice that sustains cultural identity, supports ecological resilience, and equips learners to navigate diverse knowledge worlds with critical awareness and ethical agency.